Wafer-scale 2D PtTe2 layers for high-efficiency mechanically flexible electro-thermal smart window applications. Issue 19 (6th May 2020) - Okogbue, Emmanuel; Ko, Tae-Jun; Han, Sang Sub; Shawkat, Mashiyat Sumaiya; Wang, Mengjing; Chung, Hee-Suk; Oh, Kyu Hwan; Jung, Yeonwoong
Abstract : Wafer-scale 2D PtTe2 layers exhibit superior electro-thermal properties suitable for smart window applications. Abstract : Two-dimensional (2D) transition metal dichalcogenide (TMD) layers have gained increasing attention for a variety of emerging electrical, thermal, and optical applications. Recently developed metallic 2D TMD layers have been projected to exhibit unique attributes unattainable in their semiconducting counterparts; e.g., much higher electrical and thermal conductivities coupled with mechanical flexibility. In this work, we explored 2D platinum ditelluride (2D PtTe2 ) layers – a relatively new class of metallic 2D TMDs – by studying their previously unexplored electro-thermal properties for unconventional window applications. We prepared wafer-scale 2D PtTe2 layer-coated optically transparent and mechanically flexible willow glasses via a thermally-assisted tellurization of Pt films at a low temperature of 400 °C. The 2D PtTe2 layer-coated windows exhibited a thickness-dependent optical transparency and electrical conductivity of >10 6 S m −1 – higher than most of the previously explored 2D TMDs. Upon the application of electrical bias, these windows displayed a significant increase in temperature driven by Joule heating as confirmed by the infrared (IR) imaging characterization. Such superior electro-thermal conversion efficiencies inherent to 2D PtTe2 layers were utilized to demonstrate various applications, including thermochromic displays and electrically-driven defogging windows accompanying mechanical flexibility. Comparisons of these performances confirm the superiority of the wafer-scale 2D PtTe2 layers over other nanomaterials explored for such applications.